Clinical profile and outcome of patients admitted in pediatric intensive care unit of tertiary care teaching hospital of rural North India: an observational study - Kirpal, Harita; Behl, Anuradha; Jain, Sanjana; Pandit, Saguna (International Journal of Contemporary Pediatrics, 2024)
Background: Aim of the study was to study the clinical profile of the patients admitted in the intensive care unit and their outcomes in the rural area of north India. Methods: A prospective observational study was conducted in the PICU of rural tertiary care centre over a period of one and half year. The severity of illness and outcome were analyzed using PRISM (Pediatric risk of mortality) and PIM2 (Pediatric index of mortality) scores. Results: A total of 500 patients with mean age of patients admitted in PICU was 8.08±5.56 years. The most affected system was found to be the CNS (34.80%), followed by GIT (27.40%), respiratory (17%) and various other causes (13.6%) and CVS (7.2%). There was an overall mortality of 13.40% and a survival percentage of 86.60%. Significant association was seen between various variables of PRISM and PIM2 scores. Both PRISM and PIM2 score proved with good predictors of mortality and severity of illness. However, higher value was not a sure indication of mortality. Attributed to the fact, the current scope of study leveraged into a prospective observational study with multitude of variables, multivariate analysis with random sampling was performed by SPSS 21. Significant levels were corroborated at (p<0.05) to validate mortality (outcome) based on PIM2 and PRISM scores in first place. Conclusions: The knowledge of demographic and clinical profile of the patients in a particular area and use of physiological scores can help streamline the use of limited resources in PICUs of developing countries.